Analisis Keputusan Pembelian Ogel-Ogel melalui Brand Image sebagai Variabel Mediasi - Victor Prasetya; Tri Handayani; Dala Noor Iftikhar; Yusuf Wijoyanto (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
This study aims to elaborate on the mechanism of product design, word of mouth (WOM), price perception, and product quality on purchase decisions, with brand image serving as a mediating variable. The research focuses on consumers of Ogel-Ogel, a traditional snack product from Pemalang. Utilizing a quantitative descriptive method, data were gathered from 100 respondents through purposive and accidental sampling techniques. Data analysis employed path analysis and the Sobel test to measure the strength of the mediation effect. The results reveal that, partially, all independent variables and brand image exert a positive and significant influence on purchase decisions. The most crucial finding indicates that brand image acts as an effective mediating bridge, reinforcing the transformation of physical product attributes and social recommendations into actual purchasing actions. This underscores that for MSMEs in the culinary sector, visual uniqueness and quality are insufficient without consistent brand reputation management. This research provides strategic contributions for local product managers in integrating traditional marketing elements with brand equity strengthening to navigate an increasingly competitive market.